Peran Pendidikan Agama Kristen dalam Membimbing Pertumbuhan Kepribadian Peserta Didik - Hendro H Siburian; Barcelina Christianis Siubelan; Marti Nuban (Sekolah Tinggi Teologia Kerusso Indonesia, 2024)
Researchers found that 65% of Christian students at Inpres Batnun Elementary School had poor personalities. On average, these students carry out behavior and actions that do not reflect the personality of a disciple of Christ. This is because Christian religious education at SD Inpres Batnun does not have a visible role in guiding students. In this research, the author used a qualitative descriptive method. Researchers also conducted interviews with research subjects to obtain valid data. This research aims to look at the role of Christian religious education in guiding the personality growth of students at SD Inpres Batnun. The research results show that Christian religious educators at SD Inpres Batnun do not play a good role in guiding students' personality growth. The researchers developed strategies that could be carried out by Christian religious educators at SD Inpres Batnun to guide students' personality growth.